2008
DOI: 10.1203/pdr.0b013e31817289c2
|View full text |Cite
|
Sign up to set email alerts
|

Human Meconium Has a Pulmonary Vascular and Airway Smooth Muscle Relaxant Effect

Abstract: Meconium aspiration is believed to cause persistent pulmonary hypertension syndrome of the newborn (PPHN) via vasoconstriction, whereas meconium has a relaxant effect on rat tracheal muscle. We evaluated the meconium effect on lung vascular and airway muscle. Three-days old and adult rat 3rd-4th generation arteries and adjacent bronchi were studied in vitro. Fresh homogenized meconium did not induce arterial or airway muscle contraction. In precontracted arteries, meconium induced muscle relaxation that was gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Airway smooth muscle mechanical properties were measured as previously described [22], [23]. Briefly, adult C57Bl/6 mice were sacrificed, 3 rd –4 th generation intralobar bronchial segments from the left lung were mounted in a wire myograph and isometric changes were digitized and recorded (Myodaq, Danish Myo Technology A/S, Aarhus, Denmark).…”
Section: Methodsmentioning
confidence: 99%
“…Airway smooth muscle mechanical properties were measured as previously described [22], [23]. Briefly, adult C57Bl/6 mice were sacrificed, 3 rd –4 th generation intralobar bronchial segments from the left lung were mounted in a wire myograph and isometric changes were digitized and recorded (Myodaq, Danish Myo Technology A/S, Aarhus, Denmark).…”
Section: Methodsmentioning
confidence: 99%
“…Tessler recently suggested that meconium also induced free oxygen radicals. 17 Now we describe the pathways of induction of inflammatory response following cell influx. 4 Preterm and term newborns Production of TNFa, IL1b, and IL8 is regulated by IL-10; IL-10 not detected in preterm infants with or without MAS de Beaufort et al 8 Newborn infants Overexpression of IL-8 in MAS in vitro; increased migration of neotrophils; anti-IL-8 antibodies inhibit neutrophil migration Uotila and Kaapa 9 Human monocytes In culture increase of cycloxygenase-2 expression in vitro Castellheim et al 10 Human monocytes in culture Complement activation in MAS Animal models of MAS Tyler et al 3 Animal models Surfactant inactivation, chemical pneumonitis, airway obstruction, direct toxic damage of animal lung tissues Zagariya et al 6 Rabbit pups Intense inflammatory reactions involved in meconium-induced injury in vivo; expression of endothelin 1 in MAS Davey et al 11 Piglets Acute decrease in gas exchange and dynamic lung compliance; increase of total lung protein; inhibition of surfactant Holopainen et al 12 Piglets Inflammation, airway epithelium targeted, necrotic changes, phospholipase 2 activity increased.…”
Section: Inflammatory Responses To Meconiummentioning
confidence: 99%
“…4 Preterm and term newborns Production of TNFa, IL1b, and IL8 is regulated by IL-10; IL-10 not detected in preterm infants with or without MAS de Beaufort et al 8 Newborn infants Overexpression of IL-8 in MAS in vitro; increased migration of neotrophils; anti-IL-8 antibodies inhibit neutrophil migration Uotila and Kaapa 9 Human monocytes In culture increase of cycloxygenase-2 expression in vitro Castellheim et al 10 Human monocytes in culture Complement activation in MAS Animal models of MAS Tyler et al 3 Animal models Surfactant inactivation, chemical pneumonitis, airway obstruction, direct toxic damage of animal lung tissues Zagariya et al 6 Rabbit pups Intense inflammatory reactions involved in meconium-induced injury in vivo; expression of endothelin 1 in MAS Davey et al 11 Piglets Acute decrease in gas exchange and dynamic lung compliance; increase of total lung protein; inhibition of surfactant Holopainen et al 12 Piglets Inflammation, airway epithelium targeted, necrotic changes, phospholipase 2 activity increased. Mollnes et al 13 Animal models Complement activation in MAS Khan et al 14 Mice Increase of IL-13 expression in MAS in vivo; lymphocytic and eosinophilic inflammation Zagariya et al 15 Rabbit pups Phospholipase A2 activates apoptosis, influx of T-lymphocytes and macrophages in vivo; increase of TNFa, IL-1b, IL-6 and IL-8 in MAS in vivo Zagariya et al 16 Rabbit pups Cell death by apoptosis, influx of neutrophils and macrophages in vivo Tessler et al 17 Newborn infants Reactive oxygen species in vitro…”
Section: Inflammatory Responses To Meconiummentioning
confidence: 99%
See 1 more Smart Citation
“…Results of the action of histamine in pulmonary artery in our research are not in compliance with the results of the author Tessler R with bp., which ascertains that human meconium has relaxing effect in the airways smooth musculature and vascular tissue of newborn and grown rats [32].…”
Section: Discussionmentioning
confidence: 91%